Biomechanical Comparison between Stand-alone Interbody Cages and their Benefits over Posterior Screw Fixation - Calvo-Echenique, Andrea; Cegoñino, José; Pérez-del Palomar, Amaya (Jornada de Jóvenes Investigadores del I3A, 2023)
Lumbar pain is one of the most common problems of population. Far too often it is caused by ageing and degeneration of intervertebral discs. Fusion techniques, as arthrodesis which used screw fixation, were the first surgeries used to avoid lumbar pathologies. However, arthrodesis reduced dramatically the spine movement.Stand-alone cage is a minimally invasive surgery alternative to lumbar fusion with posterior fixation. Despite their previous reported successful results (Ahmadian et al., 2014) some physicians continue questioning their effectiveness because of the risk of spine destabilization and cage migration (Oxland et al., 2000).The purpose of this research was to demonstrate that stand-alone cages introduced in a minimally invasive way are a good surgical solution for the IVD diseases.This main goal has been divided into three different partial goals: prove spinal stability, show the decompression on the neural region and compare the effects over the adjacent discs with and without posterior fixation. It is also of the interest of this work to compare between cage designs based on the above mentioned criteria.